2019
DOI: 10.2174/1874944501912010232
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Knowledge and Attitudes Towards Child Immunization in Georgia

Abstract: Background: Vaccination is the administration of a vaccine to help the immune system develop protection from a disease. It is the most cost-effective mechanism for disease prevention that allows people to have better protection from specific bacteria and viruses. Objective: The goal of the research is to determine mothers’ knowledge, attitudes and practices towards child immunization. Methods: In the framework of a cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
7
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 17 publications
6
25
7
8
Order By: Relevance
“…They reported good attitude toward childhood vaccination had been detected from 85.4% of the parents, while average and poor knowledge were detected from 11.8% and 2.7% respectively. In Georgia [13], most mothers (97%) had positive attitude toward child immunization which was slightly higher than our study outcome. Additionally, a positive attitude toward childhood immunization were also reported in a study conducted by Bamatraf & Jawass [10], which was congruent with our study result.…”
Section: Discussioncontrasting
confidence: 84%
“…They reported good attitude toward childhood vaccination had been detected from 85.4% of the parents, while average and poor knowledge were detected from 11.8% and 2.7% respectively. In Georgia [13], most mothers (97%) had positive attitude toward child immunization which was slightly higher than our study outcome. Additionally, a positive attitude toward childhood immunization were also reported in a study conducted by Bamatraf & Jawass [10], which was congruent with our study result.…”
Section: Discussioncontrasting
confidence: 84%
“…Majority of respondents (91.1%) said that they received information concerning with knowledge on routine immunization from local health personnel in the present study. Previous studies done in different countries also reported that the main source of information was either health staff [10,13,19] or health centre [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Epi Info version 7 software was used in sample size calculation where an estimated proportion of mothers who had good knowledge on routine childhood immunization was assumed to be 75% [8,9,13], confidence level 95% and confidence limit (precision) 5%. So minimum sample size requirement was 288 mothers who had 18 to 23 months old child.…”
Section: Sample Size Determination and Samplingmentioning
confidence: 99%
“…Hal ini membuktikan bahwa tidak ada pengaruh status pekerjaan ibu terhadap perilaku ibu dalam pemenuhan kebutuhan imunisasi dasar lengkap di pelaksanaan kegiatan posyandu pada klinik Annisa Kabupaten Banyuasin. Baik ibu yang bekerja maupun tidak bekerja sama-sama berusaha umtuk memenuhi kebutuhan imunisasi dasar lengkap bagi anaknya.Penelitian ini sejalan dengan penelitian Verulava yang menyatakan status pekerjaan ibu berpengaruh terhadap perilaku ibu dalam pemenuhan imunisasi (Verulava, et al,. 2019).…”
Section: Pembahasanunclassified